The Shi‘a in Modern South Asia: Religion, History, and Politics By Justin Jones and Ali Usman Qasmi, eds. (Delhi: Cambridge University Press, 2015. 212 pages.) (American Journal of Islam and Society, 2016)
The volume at hand brings together recent advances in and new avenues forthe study of both Ithna ‘Ashari and Isma‘ili Shi‘ism in South Asia. As FrancisRobinson notes in his introduction, the region’s roughly 60 million Shi‘aswere grossly neglected in scholarship until the mid-1980s. Since then, andparticularly from the turn of the twenty-first century onward, the situation haschanged significantly. Indeed, some of the most interesting and promising recentstudies of various historical and contemporary aspects of Shi‘ism in generalhave focused on those very communities. Justin Jones, one of the spearheadsof this development, has acted as co-editor of this important collectionof eight thematically highly diverse essays.After Robinson’s overview of the field’s existing literature and the volume’scontents, Sajjad Rizvi tackles a major desideratum in the study of IndianShi‘i scholarly history by closely examining the life and works of Sayyid DildarAli Nasirabadi (d. 1820). A major scholar of his day, as well as the founderof a scholarly dynasty and an instrumental figure in establishing the Usuli traditionin the Shi‘i state of Awadh, his figure and works have, surprisingly, onlyreceived attention in the context of Dildar Alis’s polemics against Shah Abdal-Aziz of Delhi (d. 1823) and his critique of Shi‘ism. Reviewing Ali’s severelycontested but lastingly influential intellectual attack on Akhbarism, Sufism,Sunnism, and philosophy, all expressed in the context of rising Shi‘ipower in late eighteenth-century Awadh, Rizvi aptly highlights the importanceof seriously considering major developments in the late pre-colonial periodin order to more fully understand the actual and supposed transformations thatSouth Asian Shi‘ism underwent during and beyond colonial rule. Needless tosay, this also holds true for the study of other Muslim communities of thenineteenth and twentieth centuries ...